Urban Systems Between the Environment, Human Health and Society: An Overview - Carlo Modonesi; Stefano Serafini; Alessandro Giuliani (Systems)
This work underlines an analogy between urban and biological systems. The dialogic approach of systems biology showed us that parts constitute a whole and, in turn, the whole constitutes the parts. The development of a biological system such as an animal or a plant does not unfold by means of an autonomous internal program. Rather, it stems from the interaction of the organism’s internal response pattern and its external environment. The wide scientific literature on the genome–environment interaction confirms this. Nevertheless, the scientific community still tends to consider the environment as a mere external factor which simply modulates the organism’s program. On the contrary, the environment has a key role in development. For example, when a seed germinates after heavy rain, it does not simply react to an external signal indicating favorable conditions for germination. Rather, it interacts directly with rainwater, which becomes a developmental factor no less important than the seed coat proteins. Similar to what happens during the development of an organism, the interface between any complex system and its environment determines its structural and functional fate. We argue that large cities have blurred the interface with their natural environment and depend on delocalized global sources. They are like organisms kept alive by external devices. Hence, we propose to regenerate a vital interface between cities and their rural and natural environment as the main and promising path towards future urban civilization.